Raziskovanje v družinski medicini v Sloveniji - Petek Šter, Marija (Zdravniški vestnik, 2018)
The primary level of health care represents an entry point into the health system, and the quality and economic sustainability of the healthcare system largely depend on it. Research is the driving force of professional development aimed at providing the best quality of patient care. Family medicine in Slovenia represents the largest specialty at the primary level of health care, which has achieved great success in the field of research in recent decades. The overview shows the characteristics of family medicine research, its inclusion into the educational process and practical work at different levels, pointing out the challenges that await family medicine as a scientific and research discipline in the future.
Keywords: družinska medicina; family medicine; institute; inštitut; raziskovanje; research